The Kuthodaw Pagoda, Myanmar: collaborative conservation of a UNESCO Memory of the World site. Issue 1 (2nd January 2018) - Reade, Wendy J.
Abstract : The Kuthodaw Pagoda complex in Mandalay, Myanmar is listed on the UNESCO Memory of the World Register, valuable for its 729 marble stelae each housed in a white-washed mini-pagoda and inscribed with Theravāda Buddhist texts written in Pali, and known as the 'World's Biggest Book'. In 2013 Australia's Nan Tien Institute, Wollongong, and the University of Sydney worked with the Myanmar Ministry of Culture, the Mandalay Department of Archaeology and the custodians of the Kuthodaw Pagoda site to conserve, photograph, digitise and make a freely available database for the study of the inscribed texts. This paper describes the collaborative conservation project that included condition assessment, documentation, conservation work to the stelae and site, local staff training, and provision of a practical maintenance plan. The successful development and execution of this preservation project was due to a productive cultural dialogue that was based on consultative discussion between all parties, willingness to co-operate, and consideration of Buddhist customs, traditional crafts, local practice, and the impact of visitors and natural agencies on the site.